The Effect of Variation Orders on Project Cost and Schedule Overruns - Smith, Wouter (Stellenbosch : Stellenbosch University, 2016)
ENGLISH ABSTRACT: Cost and schedule overruns are common occurrences in construction projects, regardless of the various studies that have been done on the subjects. These overruns can occur for a wide variety of reasons; most of these reasons however can be attributed to scope change. The General Conditions of Contract for Construction Works use Variation Orders (VO’s) to deal with scope changes. Where other studies have focussed only on cost overruns and their causes, or schedule overruns and their causes, this research uses information collected about VO’s to determine the role of changes on the project schedule and costs. A database of 137 projects which were completed within the last 10 years has been investigated in order to determine if the number of VO’s or timing of VO’s have any effect on the project cost and schedule overruns. The Western Cape Department of Transportation and Public Works was the client for all the projects, thus only public transportation projects were studied. The research finds that projects with more VO’s have larger cost and schedule overruns than those with less VO’s. Additionally it also finds that larger cost and schedule overruns occur when the VO’s occur later in the project.